Numerical study of exhaust flow behavior in a calcium carbide waste adsorber for two-wheel vehicle applications - H.S. Tira; Y.A. Padang; N. Kaliwantoro; A.D. Catur; I.G.N.K. Yudhyadi; S. Rahman (Dinamika Teknik Mesin, 2026)
Calcium carbide waste has demonstrated potential as an adsorber material for motorcycle exhaust emission control; however, the internal flow and thermal mechanisms governing its performance remain unclear. This study presents a computational fluid dynamics (CFD) analysis of exhaust gas flow through a calcium carbide waste adsorber to elucidate pressure, velocity, temperature, and turbulence characteristics. Simulations were conducted for adsorber lengths of 50, 100, and 150 mm, with the 150 mm configuration selected as a representative case due to similar overall trends. The results indicate a gradual pressure reduction along the exhaust system, flow acceleration within the adsorber due to cross-sectional constriction, and non-uniform temperature distribution influenced by asymmetric flow patterns. Turbulence kinetic energy increases upon gas entry into the adsorber and varies with adsorber length, highlighting the role of geometry in flow mixing and turbulence dissipation. These findings provide physical insight into the mechanisms underlying the emission reduction observed in previous experimental studies.